Relationship between human capital, new venture ideas, and opportunity beliefs: A meta‐analysis - Canavati, Sergio; Libaers, Dirk; Wang, Tang; Hooshangi, Soheil; Sarooghi, Hessam (Strategic Entrepreneurship Journal, 2021)
Abstract Research summary We meta‐analyze the structural relationship between human capital, the ability to generate new venture ideas, and the favorability of opportunity beliefs to address divergent theoretical predictions and inconsistent empirical findings. We test a two‐stage process model of entrepreneurial opportunity identification, distinguishing between the ability to generate new venture ideas and the favorability of third and first‐person opportunity beliefs. We also distinguish between two categories of human capital: general and specific human capital. Our results suggest that general and specific human capital are positively associated with the ability to generate new venture ideas. Furthermore, only specific human capital matters in influencing the favorability of opportunity beliefs, yet the ability to generate new venture ideas is far more important than human capital for the favorability of opportunity beliefs. Managerial summary How does an individual's human capital relate to the attractiveness of opportunities identified? In this study, we review the body of literature on this topic and analyze the relationships between two types of human capital—general and specific human capital, the ability to generate new venture ideas, and the attractiveness of opportunities. We find that both general human capital—primarily education and work experience—and specific human capital—industry and entrepreneurial experience—are useful for generating new venture ideas. However, only specific human capital is useful when assessing which new venture ideas can turn into attractive opportunities. We also find that the ability to generate new venture ideas is more strongly associated with the attractiveness of opportunities than either type of human capital.